Analisis Kestabilan Lereng dengan Pendekatan Probabilitas Longsor pada Penambangan Batubara Pit 8an East Block PT Indominco Mandiri - Ilham Firmansyah; Barlian Dwinagara; Untung Sukamto; Bagus Wiyono; Tedi Agung Cahyadi (Retii, 2020)
The stability analysis of the design of the mining slope at Pit 8AN East Block PT. Indominco Mandiri refers to the old regulation, namely using the Safety Factor in determining the slopes are safe or not. Meanwhile, according to the Minister of Energy and Mineral Resources Decree No. 1827 K/30/MEM In 2018, the determination of safe slopes or not is based on the Safety Factor (SF) and the Probability of Failure (PoF). This research was conducted to analyze the stability of the final pit slope design so that the slope design can be categorized as safe or unsafe. Based on geotechnical investigations and field observations, the types of failure that occur are a circular failure for slopes highwall and plane failure for slopes lowwall. Slope stability analysis using the limit equilibrium method (Bishop Simplified) assisted by software Slide v.8.0 (Rocscience). Meanwhile, the probability of failure analysis uses the Monte Carlo method. Based on the analysis, it is known that the design of the final mining slope, both Slope A and Slope B, are categorized as safe. Variations were made to the design of the two final mining slopes by increasing the overall slope angle. On slope A by increasing the angle of the single-slope and on slope B by reducing the width of the berm. Thus, the value of the slope safety factor decreases to be more than or equal to 1.3, and the probability of failure value increases to a maximum limit of 10%. The impact of slope optimization is an increase in coal reserves. Keywords: Limit Equilibrium Method, Safety Factor, Probability of Failure, Slope A, Slope B